2020
DOI: 10.15407/ubj92.05.062
|View full text |Cite
|
Sign up to set email alerts
|

DNA loop domain rearrangements in blast transformed human lymphocytes and lymphoid leukaemic Jurkat T cells

Abstract: Chromatin loops are important elements of both chromatin higher-order structure and transcription regulation system. Our previous works showed that several features of the loop domain organization could be investigated by single cell gel electrophoresis (the comet assay) using the kinetic approach. In this study we applied this technique to study DNA loop domain organization in lymphoid cells: human lymphocytes, lymphoblasts cultivated during 24 h and 44 h, and t cells of Jurkat cell line. two features of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
(54 reference statements)
0
2
0
Order By: Relevance
“…In present study, we analyzed DNA loop reorganization in T98G and U373 glioblastoma cell lines in the setting of serum deprivation/restoration. For both serum-free cell cultures, the fraction of DNA in the surface loops is practically identical and coincides within the error with this parameter obtained, for example, for intact lymphocytes [9,10].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In present study, we analyzed DNA loop reorganization in T98G and U373 glioblastoma cell lines in the setting of serum deprivation/restoration. For both serum-free cell cultures, the fraction of DNA in the surface loops is practically identical and coincides within the error with this parameter obtained, for example, for intact lymphocytes [9,10].…”
Section: Discussionsupporting
confidence: 86%
“…This reorganization consists of an almost 1.5-fold increase in the fraction of DNA in the inner loops and a 2-fold increase in their size. It is curious that similar changes (an increase in the size of internal loops and the relative DNA amount in their composition) were also observed upon activation of lymphocytes by interleukin-2 [9]. The absence of visible changes in the amount of DNA in the comet tails and the contour length of the loops in U373 cells shows apparently that the inner loops in these cells are too large under any conditions.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…After a long-time electrophoresis the relative amount of DNA in the tails reached ~20 % (first two subsets together) for human lymphocytes [19]. For less differen tiated cancer cells of different types the saturation level of DNA in the tails was much lower [20,22,23], i.e., there was a large amount of DNA in the very long loops. At the same time, the kinetic plots of DNA exit usually had a two-step shape (the two steps were attributed to first two subsets of the loops before, the second step was absent: the plots can be fitted with the standard equation (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Measuring the kinetics of DNA exit during the co met assay we have shown that DNA loops in the nucleoids (cells lysed in the presence of detergents and high salt) correspond to chromatin loops in living cells [19][20][21]. We have shown also that the kinetic behavior of the two parameters, the relative amount of DNA in the comet tail and the tail length, depend on the cell type and/or the cell functional state [20,22,23].…”
Section: Structure and Function Of Biopolymersmentioning
confidence: 91%